ANALISIS PENGARUH PROFITABILITAS,EPS DAN PER TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN DI BEI:SEBAGAI DASAR PENGAMBILAN KEPUTUSAN INVESTASI - Sari, Ni Made Dewi Puspita; Triaryati, Nyoman (E-Jurnal Manajemen; Vol 4 No 3 (2015), 2015)
The Company issued stock to meet the needs of its funding, while investors who invest funds in the stock has a goal to get a return that can be either capital gains or dividend. Investing in stocks at high risk, to minimize risk and obtain optimal return, in addition to the necessary technical analysis also fundamental analysis. Analysis of companies basing decisions of investors to assess whether the relevant company stock is undervalued or overvalued. This study aimed to determine the effect of return on equity, Earning Per Share and Price Earning Ratio of Company Stock Price Banking in Indonesia Stock Exchange 2010-2013. Sampling technique was used purposive sampling, with secondary data such as annual financial statements Banking Company during the study period. This study uses multiple linear regression analysis technique. The results of this study indicate that the ROE, EPS and PER partially positive and significant effect on stock prices Banking companies in Indonesia Stock Exchange 2010-2013.
Keywords: ROE, EPS, PER, stock price